Complications and Revisions After Spine Surgery in Patients With Skeletal Dysplasia: Have We Improved?. Issue 2 (March 2023) - Shafi, Karim; Lovecchio, Francis; Sava, Maria; Steinhaus, Michael; Samuel, Andre; Carter, Erin; Lebl, Darren; Farmer, James; Raggio, Cathleen
Study Design: Retrospective case series. Objective: To report contemporary rates of complications and subsequent surgery after spinal surgery in patients with skeletal dysplasia. Methods: A case series of 25 consecutive patients who underwent spinal surgery between 2007 and 2017 were identified from a single institution's skeletal dysplasia registry. Patient demographics, medical history, surgical indication, complications, and subsequent surgeries (revisions, extension to adjacent levels, or for pathology at a non-contiguous level) were collected. Charlson comorbidity indices were calculated as a composite measure of overall health. Results: Achondroplasia was the most common skeletal dysplasia (76%) followed by spondyloepiphyseal dysplasia (20%); 1 patient had diastrophic dysplasia (4%). Average patient age was 53.2 ± 14.7 years and most patients were in excellent cardiovascular health (88% Charlson Comorbidity Index 0-4). Mean follow up after the index procedure was 57.4 ± 39.2 months (range). Indications for surgery were mostly for neurologic symptoms. The most commonly performed surgery was a multilevel thoracolumbar decompression without fusion (57%). Complications included durotomy (36%), neurologic complication (12%), and infection requiring irrigation and debridement (8%). Nine patients (36%) underwent a subsequent surgery. Three patients (12%) underwent a procedure at a non-contiguous anatomic zone, 3 (12%) underwent a revision of the previous surgery, and another 3 (12%) required extension of their previous decompression or fusion. Conclusions: Surgical complication rates remain high after spine surgery in patients with skeletal dysplasia, likely attributable to inherent characteristics of the disease. Patients should be counseled on their risk for complication and subsequent surgery.